2014
DOI: 10.1039/c4cp02025a
|View full text |Cite
|
Sign up to set email alerts
|

Examination of surface phenomena of V2O5loaded on new nanostructured TiO2prepared by chemical vapor condensation for enhanced NH3-based selective catalytic reduction (SCR) at low temperatures

Abstract: In this article, we describe the investigation and surface characterization of a chemical vapor condensation (CVC)-TiO2 support material used in a V2O5/TiO2 catalyst for enhanced selective catalytic reduction (SCR) activity and confirm the mechanism of surface reactions. On the basis of previous studies and comparison with a commercial TiO2 catalyst, we examine four fundamental questions: first, the reason for increased surface V(4+) ion concentrations; second, the origin of the increase in surface acid sites;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Liu et al [14] reported that Ti 3+ creates a free carrier (%electron) when oxidized to Ti 4+ . In addition, according to previous studies by Cha et al [13,16], the TiO 2 synthesized via CVC had a higher ratio of Ti 3+ ions and contained more free carriers, and had a clear effect on the oxide ion state of the loading material. We also thought that this was the reason for the higher ratio of Ce 3+ ions; CVC-TiO 2 has more free carriers on the material surface.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Liu et al [14] reported that Ti 3+ creates a free carrier (%electron) when oxidized to Ti 4+ . In addition, according to previous studies by Cha et al [13,16], the TiO 2 synthesized via CVC had a higher ratio of Ti 3+ ions and contained more free carriers, and had a clear effect on the oxide ion state of the loading material. We also thought that this was the reason for the higher ratio of Ce 3+ ions; CVC-TiO 2 has more free carriers on the material surface.…”
Section: Resultssupporting
confidence: 56%
“…XPS Ti 2p spectra of pure TiO 2 catalysts. This figure was prepared by using XPS data from a previous paper by Cha et al [13] Figs. 5 and 6 show the XPS V 2p spectra of V 2 O 5 -CeO 2 /TiO 2 catalysts with only V 2 O 5 loaded on each TiO 2 support material (V 2 O 5 / TiO 2 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5b,c) compare with pure TiO 2 and apure TiO 2 (see Fig. S13), it can be observed that, besides the peak of Ti-O, its IR spectra displays additional features corresponding to two distinct NH 3 species: bands at 3340 and 1600 cm −1 , they are assigned to adsorb NH 3 on Lewis acid sites 53,54 .…”
Section: Discussionmentioning
confidence: 98%